2022
DOI: 10.3390/ijms23084330
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Novel Roles of Salivary Exosomes in the Regulation of Human Corneal Stromal Cell Migration and Wound Healing

Abstract: Salivary exosomes have demonstrated vast therapeutic and diagnostic potential in numerous diseases. This study pioneers previously unexplored roles of SE in the context of corneal wound healing by utilizing primary corneal stromal cells from healthy (HCFs), type I diabetes mellitus (T1DMs), type II DM (T2DMs), and keratoconus (HKCs) subjects. Purified, healthy human SEs carrying tetraspanins CD9+, CD63+, and CD81+ were utilized. Scratch and cell migration assays were performed after 0, 6, 12, 24, and 48 h foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Moreover, EVs have been found to be secreted in the cornea following wounding [ 41 ] and it is known that exosomes secreted by corneal epithelial cells can pass through the BM if impaired by an injury [ 41 ]. These results all pointed to a potential role of exosomes in corneal wound healing, which has recently been the focus of a few studies [ 41 , 42 , 45 , 46 , 47 , 48 ]. However, characteristics, functional roles and mechanisms of action of corneal exosomes remain to be fully investigated.…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, EVs have been found to be secreted in the cornea following wounding [ 41 ] and it is known that exosomes secreted by corneal epithelial cells can pass through the BM if impaired by an injury [ 41 ]. These results all pointed to a potential role of exosomes in corneal wound healing, which has recently been the focus of a few studies [ 41 , 42 , 45 , 46 , 47 , 48 ]. However, characteristics, functional roles and mechanisms of action of corneal exosomes remain to be fully investigated.…”
Section: Introductionmentioning
confidence: 68%
“…257 Additionally, neurodegenerative diseases were given much attention for saliva exosome biomarker discovery. 258 There have been reviews summarizing salivary exosomal biomarkers in cancer, [259][260][261][262][263] neurodegenerative diseases, 264 mental diseases, 265 systematic disease, 266 wound healing 267,268 and isolation methods. 269,270 Research articles emphasize protein biomarkers 250,257,[271][272][273][274][275] and RNA markers.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%
“…There have been reviews summarizing salivary exosomal biomarkers in cancer, 259 263 neurodegenerative diseases, 264 mental diseases, 265 systematic disease, 266 wound healing 267 , 268 and isolation methods. 269 , 270 Research articles emphasize protein biomarkers 250 , 257 , 271 275 and RNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…Widyaningrum et al [ 96 ] found that the platelet extracellular vesicles (PEVs) could increase the viability, wound-healing rate, as well as the proliferation markers of corneal endothelial cells, which represents a novel regenerative biotherapy for corneal endothelial dysfunction. The healthy human exosomes were also found to positively regulate the migration of human corneal stromal cell and wound healing in a recent study by Escandon et al [ 97 ]. The studies summarized above clearly support the tremendous potential of EVs for regenerative medicine applications; however, further investigations in animals still need to be carried out for clinical translation.…”
Section: The Classification Of Bioinspired Nanostructured Systemsmentioning
confidence: 99%